Process optimization for Cr(VI) adsorption onto activated carbons by experimental design - Ozdemir, Ercan; Duranoglu, Dilek; Beker, Ulker; Avci, Asli Ozge (ELSEVIER SCIENCE SA, 2011)
A study on the adsorption of Cr(VI) onto raw and modified activated carbons was conducted and the process parameters were optimized using Response Surface Methodology (RSM). Apricot stones have been converted to microporous activated carbon with considerably high surface area (1462 m(2) g(-1)) by phosphoric acid activation. Produced carbons have been characterized by using different physicochemical methods. In order to determine the effects of process parameters namely temperature (20-60 degrees C), initial solution pH (2-6) and initial Cr(VI) concentration (30-60 mg L-1) on Cr(VI) uptake from aqueous solution, a three-level, three-factor, Box-Behnken design has been employed. The second order mathematical model was developed by regression analysis of the experimental data obtained from 17 batch runs. The optimum pH, temperature and initial concentration were found to be 2.0, 60 degrees C, and 60 mg L. respectively. Cr(VI) adsorption capacity was 262 mg g(-1) at the optimum combination of process parameters. The enthalpy change of Cr(VI) adsorption was found to be 54.05 kJ mol(-1). Dynamic adsorption data were applied to pseudo-first-order and pseudo-second-order rate equations. Pseudo-second-order kinetic model well expressed Cr(VI) adsorption onto activated carbon. The results of both thermodynamic and kinetic study indicated the chemical interaction between Cr(VI) species and surface functional groups on carbon surface. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chromium removal; Activated carbon; Box-Behnken Response Surface; Methodology; Experimental design; Process optimization; AQUEOUS-SOLUTIONS; HEXAVALENT CHROMIUM; REMOVAL; KINETICS; BIOSORPTION; ADSORBENTS; WASTE; WATER; Engineering